Proceedings of XV Modave Summer School in Mathematical Physics — PoS(Modave2019) 2020
DOI: 10.22323/1.384.0003
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Symmetries in the Gauge fixing Approach and the BMS group

Abstract: These notes are an introduction to asymptotic symmetries in gauge theories, with a focus on general relativity in four dimensions. We explain how to impose consistent sets of boundary conditions in the gauge fixing approach and how to derive the asymptotic symmetry parameters. The different procedures to obtain the associated charges are presented. As an illustration of these general concepts, the examples of fourdimensional general relativity in asymptotically (locally) (A)dS 4 and asymptotically flat spaceti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(92 citation statements)
references
References 152 publications
(263 reference statements)
0
69
0
Order By: Relevance
“…generalized Killing equation), 4) Compute the surface charge integral with those parameters (to get a differential charge), and 5) Integrate the differential charge on phase space. In the present notes we extensively explore the first 2 See for instance a recent review about the equivalence among the Iyer-Wald and Barnich-Brandt procedure [13]. Analogously, in [14] was shown that the of-shell Abbot-Deser-Tekin formalism is related to the Iyer-Wald and Barnich-Brandt-Compére formalism.…”
Section: Contentsmentioning
confidence: 91%
See 2 more Smart Citations
“…generalized Killing equation), 4) Compute the surface charge integral with those parameters (to get a differential charge), and 5) Integrate the differential charge on phase space. In the present notes we extensively explore the first 2 See for instance a recent review about the equivalence among the Iyer-Wald and Barnich-Brandt procedure [13]. Analogously, in [14] was shown that the of-shell Abbot-Deser-Tekin formalism is related to the Iyer-Wald and Barnich-Brandt-Compére formalism.…”
Section: Contentsmentioning
confidence: 91%
“…A further analysis allows for the obtained quantity to be interpreted as the entropy of the black hole. Here we stress that although the formula simplifies on the bifurcated horizon, one is also able to compute the same value for the entropy outside the horizon, on an arbitrary closed surface containing the black hole singularity, by using the full formula (3.25) 13 . The reason is that the full formula is protected by the conservation while the Noether potential is not.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…The symplectic structure is defined in two steps. First, the presymplectic form is defined from covariant phase space methods [72][73][74] as we shortly review (see also [40,41]). Second, it is renormalized in accordance with the action [78].…”
Section: Holographically Renormalized Symplectic Structurementioning
confidence: 99%
“…In asymptotically flat Einstein gravity, leading [1][2][3], subleading/overleading [4][5][6][7][8][9][10] or higher subleading/overleading [11,12] relationships have been found in the infrared sector, which relate symmetries [5,6,9,[13][14][15][16][17][18][19][20][21], memory effects [7,12,[22][23][24][25][26][27][28][29][30][31][32][33][34][35] and scattering identities involving soft modes [36,37]. Partial reviews include [38][39][40][41]. In cosmology, such relationships have also been described [42][43][44]…”
Section: Jhep10(2020)205 Introductionmentioning
confidence: 99%